Geopolitical Reasoning. Construction of Representations and Geopolitical Codes of Chile and Its Neighbors - Garay-Vera, C (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2019)
Sin Resumen Disponible